Exosporium and Spore Coat Formation in Bacillus cereus T - Ohye, D. F. (1973)
The exosporium of Bacillus cereus T was first observed as a small lamella in the cytoplasm in proximity to the outer forespore membrane (OFSM) near the middle of the sporangium. Serial sections, various staining methods, and enzyme treatments failed to show any connections between the small lamella and the OFSM. The advancing edge of the exosporium moved toward the polar end of the cell until the spore was completely enveloped. The middle coat was formed between the exosporium and the OFSM from a three-layered single plate or “belt,” consisting of two electron-dense layers separated by an electron-transparent layer. This “belt,” usually first observed toward the center of the sporangium, developed without changing thickness or appearance over the surface of the forespore. Between the middle coat and the OFSM, a layer of cytoplasm about 50-nm thick was enclosed by the developing coat; this became the inner coat. Electron-dense material was deposited on the outer surface of the middle coat to form the outer coat.